Climate Change Hazards: Socio-economic Vulnerabilities and indigenous resilience in the Lower Karnali Watershed Region (LKWR), Bardiya, Nepal - Gurung, Samikchhya; Dhami, Yadav Singh; Aryal, Rahul; Raut, Sunita; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2026)
This paper examines climate change-induced hazards, socio-economic vulnerabilities, and traditional indigenous resilience practices in the Lower Karnali Watershed Region (LKWR), Nepal. Specifically, it focuses on Geruwa and Madhuwan among marginalized and under-represented minorities such as women, Dalits, and other indigenous ethnic groups who are highly affected by climate-related hazards and stresses. This study employs a “mixed method” approach, using household surveys (N=120), key informant interviews, and focus group discussions as data-collection tools to gather primary data. Primarily, this paper analyzes how gender, caste, and indigenous communities are affected by climatic hazards and cope with environmental stress in the study areas. Meteorological data from 1994 to 2024 are also incorporated to validate climate variability and change. In the study area, the temperature trend indicates steady warming, with minimum temperatures rising faster while maximum temperatures increase at night. Although there is little long-term linear trend in precipitation records, there is significant inter-annual variability, with drought years scattered with unexpectedly high-rainfall years. Local experiences of rising summer temperatures, erratic rainfall, declining water supplies, floods, droughts, and more volatile livelihoods are all linked to these climatic shifts. The findings highlight declining agricultural productivity, livelihood challenges, frequent flooding, river erosion, heat waves, droughts, and wildfires as major hazards resulting from climate change. While flooding remains the leading hazard in Geruwa-3, drought and river erosion severely affect Madhuwan-2. These hazards disproportionately impact the socio-economic status of the marginalized communities. To cope with climate-induced shocks and hazards, the indigenous communities in these areas, particularly the Tharu, rely heavily on traditional social-ecological knowledge such as Badhghar and Kulopani Chaudhariya water governance institutions. In this regard, this paper highlights the need to integrate indigenous practices with modern scientific approaches to create resilient and equitable long-term solutions for disasters and sustainable development.